Use of the Rehabilitation Treatment Specification System (RTSS) in the management of nitrous oxide (N2O)-induced spinal cord injury. Issue 2 (7th February 2023) - Buttery, Charlotte; Birns, Jonathan; Gibson, Jamie; Jones, Gareth David
Abstract : Nitrous oxide (N2 O) is an inhaled anaesthetic gas and a popular intoxicant. Excessive recreational use can cause spinal cord myelopathy. Previous studies have discussed the medical management. However, none have specified the sensorimotor rehabilitation management. This case report documents the investigations, physical rehabilitation and functional outcomes in two cases of N2 O-associated myelopathy. Both presented with lower limb strength and sensorimotor integration impairments resulting in ataxic ambulation. Dorsal column signal abnormality was observed on T2-weighted MRI in one case. Myelopathy was diagnosed based on clinical presentation and both were treated with vitamin B12 . Rehabilitation was conceived and specified using the Rehabilitation Treatment Specification System (RTSS). Both cases achieved independent indoor gait on hospital discharge, and full function at 9 months in one case. Appropriate and timely medical management and reasoned rehabilitation provided excellent functional outcomes for N2 O-related myelopathy. By using the RTSS, reasoned rehabilitation efficacy can be tested in the future.